Temperature Effect on Traditional Pear (Pyrus communis L.) Landraces Seed Germination - Jordanovska, Suzana; Milevska, Elizabeta Miskoska (Sciencedomain International, 2018)
Investigations included six traditional pear landraces (Pyrus communis L.): Aleksandra, Vodenka, Patlidjanka, Ljubichica, Tatlikuti and Crvenushka. The number of seeds per fruit, seed energy and total seed germination were investigated and statistically analyzed (P = .05 and P = .01). Seed stratification encompassed pre-chilling by using three treatments: I treatment covers seed pre-chilling at -18 C/T for 24 hours; II treatment covers seed pre-chilling at +1 C/T for 2 weeks; III treatment covers seed pre-chilling at +8 C/T for 1 week. Only Patlidjanka belongs to the group with high seed number in the fruit. The other landraces produced low seed number like 2-3 seeds per fruit. The average number of all researched landraces is 3.67 seeds per fruit. The pear Tatlikuti showed a very high significant difference (P = .01). It was concluded that III treatment showed the highest seed energy at landraces Ljubichica 77.5% and Tatlikuti 75.0% and the lowest at Aleksandra 52.5%. There were significant differences (P =.05) between applied treatments regarding seed energy. In II treatment, the total seed germination had the highest effect on Patlidjanka 87.75%. The values for germination seeds in the other landraces were in the range from 77.5% to 86.25%. Statistically, a significant difference was determined in the landraces Ljubichica and Crvenushka (P = .05), and there was high significant difference (P = .01) in the pear Aleksandra. The II and III treatment could be recommended as the most suitable to improve the pear seed germination.
Keywords: Pear, Pyrus communis L., traditional landraces, seed stratification, seed number per fruit, total germination